ANTIBACTERIAL ACTIVITIES OF BACTERIAL SYMBIONTS OF SOFT CORAL Sinularia sp. AGAINST TUBERCULOSIS BACTERIA - S. Sulistiyani; Sri Achadi Nugraheni; Ocky Karna Radjasa; Agus Sabdono; Miftahuddin Majid Khoeri (JOURNAL OF COASTAL DEVELOPMENT, 2010)
Tuberculosis (TB) is caused by Mycobacterium tuberculosis. Although TB is a curable disease, it continues tobe one of the most important infectious causes of death worldwide. Indonesia ranks 3rd on the list of TB highburden countries in the world with 86,000 cases deaths and the Multi Drug Resistant Tuberculosis (MDR TB)estimated cases in Indonesia is 10,000. This research was aimed to isolate and characterize of soft coralSinularia sp.-associated bacteria having antibacterial activity against Tuberculosis bacteria. There were109 isolates collected from Sinularia sp. Two isolates from Sinularia sp.-associated bacteria, SC4TGZ3 andSC4TGZ4 were successfully screened for antibacterial against Tuberculosis bacteria. SC4TGZ3 was found toinhibit the growth of MDR TB strain HE, MDR TB strain SR and H37Rv. Whereas, SC4TGZ4 was found toinhibit the growth of MDR TB strain HE. Based on PCR amplification 16S rDNA softcoral bacateria wereidentified as follows: SC4TGZ3 was closely related to Pseudovibrio sp. and SC4TGZ4 was closely related toAlpha proteobacterium sp.